Chronic hypoxia changes gene expression profile of primary rat carotid body cells: consequences on the expression of NOS isoforms and ET-1 receptors - Mosqueira, Matias; Iturriaga, Rodrigo (Physiological genomics, 2019)
Sustained chronic hypoxia (CH) produces morphological and functional changes in the carotid body (CB). Nitric oxide (NO) and endothelin-1 (ET-1) play a major role as modulators of the CB oxygen chemosensory process. To characterize the effects of CH related to normoxia (Nx) on gene expression, particularly on ET-1 and NO pathways, primary cultures of rat CB cells were exposed to 7 days of CH. Total RNA was extracted, and cDNA-32P was synthesized and hybridized with 1,185 genes printed on a nylon membrane Atlas cDNA Expression Array. Out of 324 differentially expressed genes, 184 genes were upregulated, while 140 genes were downregulated. The cluster annotation and protein network analyses showed that both NO and ET-1 signaling pathways were significantly enriched and key elements of each pathway were differentially expressed. Thus, we assessed the effect of CH at the protein level of nitric oxide synthase (NOS) isoforms and ET-1 receptors. CH induced an increase in the expression of endothelial NOS, inducible NOS, and ETB. During CH, the administration of SNAP, a NO donor, upregulated ETB. Treatment with Tezosentan (ET-1 receptor blocker) during CH upregulated all three NOS isoforms, while the NOS blocker L-NAME induced upregulation of iNOS and ETB and downregulated the protein levels of ETA. These results show that CH for 7 days changed the cultured cell CB gene expression profile, the NO and ET-1 signaling pathways were highly enriched, and these two signaling pathways interfered with the protein expression of each other.
Gesehen am 21.05.2019